Impact of Savings and Credit Unions on Productivity: The Case of Cajamarca - Mendoza Vargas, Oscar Manuel (2025)
The Savings and Credit Unions, UNICA, are a financial inclusion policy promoted by the Development Bank of Peru in partnership with other institutions since 2008. In the case of Cajamarca, Los Andes Association, a corporate body of Newmont Yanacocha, was the allied. The research measures the incidence of the UNICA on agricultural productivity at the provincial level, for this a database of 5 823 records from 2004 to 2023 was prepared at the level of agricultural units and a Kremer (1993) stochastic production function type with iterative fixed effects is estimated, where the incidence is established through three channels: 1) Access to credit increases productivity by 0,7951%, 2) an increase in the capital accumulation index of the UNICA at the provincial level of 1,00% generates increases in productivity of 0,1703% and 3) an increase in the ratio of beneficiaries to partners of 1,00% will reduce agricultural productivity by – 0,1657%; this result is counterproductive and requires further investigation.